Analisis Fundamental Laporan Keuangan PT Bank Mandiri (Persero) Tbk dan Analisis Tren dalam Pengambilan Keputusan Investasi - Putri, Citra Amelia (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2023)
Fundamental analysis is an important thing that investors need to do before carrying out their investment activities. This analysis is carried out to minimize the risk of the global economy, which significantly influences the desires of a company. Fundamental analysis is enhanced by using trend analysis to assess a company’s projections to see future risks. This research was conducted to determine and determine the financial performance of PT Bank Mandiri (Persero) Tbk and its growth projections through fundamental and trend analysis. The expected achievements of this research can be used as a learning medium and become an illustration of investment considerations in stock securities in the banking sector. This research was conducted using quantitative descriptive research methods using secondary data in the form of macroeconomic information, financial reports, annual reports, and sustainability reports of PT Bank Mandiri (Persero) Tbk for the 2019-2022 period. This research shows that PT Bank Mandiri (Persero) Tbk has good financial performance starting from PER, PBV, DER, CAR, ROA, and ROE. The valuation of Bank Mandiri shares for 2019-2022 is undervalued based on the PER approach, and investment decisions should be made by buying these shares. PT Bank Mandiri’s optimal performance is also demonstrated by the revenue and net profit trend, which is predicted to continue to increase over the next five years amidst economic turmoil.